2016
DOI: 10.1007/s00442-016-3758-3
|View full text |Cite
|
Sign up to set email alerts
|

Brevicoryne brassicae aphids interfere with transcriptome responses of Arabidopsis thaliana to feeding by Plutella xylostella caterpillars in a density-dependent manner

Abstract: Plants are commonly attacked by multiple herbivorous species. Yet, little is known about transcriptional patterns underlying plant responses to multiple insect attackers feeding simultaneously. Here, we assessed transcriptomic responses of Arabidopsis thaliana plants to simultaneous feeding by Plutella xylostella caterpillars and Brevicoryne brassicae aphids in comparison to plants infested by P. xylostella caterpillars alone, using microarray analysis. We particularly investigated how aphid feeding interferes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 80 publications
0
34
0
Order By: Relevance
“…Research has increasingly shifted from studying the effects of single to multiple herbivore attack on plant defence mechanisms. Increasing the complexity of the studied interactions can have strong and unpredictable consequences for plant–insect interactions (Dicke et al ), and it is clear that our knowledge of how insect species interact individually with a plant is insufficient to predict the effects of combined herbivore attack at the transcriptional level all the way up to the community level, particularly when the herbivores are of different feeding guilds (de Rijk et al ; Kroes et al in press; Mathur et al ; Stam et al ; Voelckel & Baldwin ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has increasingly shifted from studying the effects of single to multiple herbivore attack on plant defence mechanisms. Increasing the complexity of the studied interactions can have strong and unpredictable consequences for plant–insect interactions (Dicke et al ), and it is clear that our knowledge of how insect species interact individually with a plant is insufficient to predict the effects of combined herbivore attack at the transcriptional level all the way up to the community level, particularly when the herbivores are of different feeding guilds (de Rijk et al ; Kroes et al in press; Mathur et al ; Stam et al ; Voelckel & Baldwin ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effects of dual attack or herbivore density on global transcriptome changes have recently been initiated (e.g. Davila Coolen et al 2016, Kroes et al 2017), but the effects on metabolome changes are scarce (Jansen et al 2009;Maag et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a study system, we used Brassica oleracea plants and their interaction with several specialist insect herbivores. This system has been previously used to study interactions between folivorous insects (Kroes, van Loon, & Dicke, 2015) and transcriptomic responses to various insects on leaves (Kroes et al, 2017, Sarde et al, 2010. Furthermore, in a closely related plant species, Brassica nigra, Pieris brassicae caterpillars were found to negatively affect the root-chewing herbivore Delia radicum, the cabbage root fly (Soler et al, 2007).…”
mentioning
confidence: 99%
“…The A. thaliana-insect interaction is a model system used to demonstrate the defense resistance of plants to leaf chewers, particularly the analysis of cellular changes at gene/proteomic levels (Kliebenstein et al 2002;Collins et al 2010;Truong et al 2015;Kroes et al 2017). Recently, Kroes et al (2017) observed the upregulation of various JAresponsive genes in response to feeding by P. xylostella caterpillar, by a microarray analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kroes et al (2017) observed the upregulation of various JAresponsive genes in response to feeding by P. xylostella caterpillar, by a microarray analysis. The protein expression changes in A. thaliana leaves due to P. xylostella infestation were identified by two-dimensional gel electrophoresis (2-DE) coupled with mass spectrometry in several studies (Collins et al 2010;Liu et al 2010).…”
Section: Introductionmentioning
confidence: 99%